(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1997)
The Tirana Depression is located in the eastern and inner part of the Periadriatic Depression.It forms an elongated NW-SE oriented structural element,60 km in length, located between the front of west -verging Dinaric structures and the east-verging Paper Rova anticline-Preze homocline alignment, which acted as a back-thrust till post-Pliocene age. Some significant stratigraphic sections were examinated mainly south of Tirana on the eastern and western limbs of a wide syncline.Physical and micropaleontological data, including marker levels,unconformities and planktonic foraminifera content were used to correlate the sections. Two Lithothamnium levels, uppermost Langhian and Serravallian, were esed markers. The generalized occurence of planktonic Foraminifera- bearing mudstones,uppermost Serravallian-Tortonian in age,is interpreted as significant.The Langhian and Serravallian uncoformities, recognizable at the base of the Lithothamnium limestone levels,are thought to be of regional importance. Continental and shallow marine sediments are largely prevailing. Deep-marine sediments are limited to the Oligocene-earliest Miocene and Serravallian-Tortonian p.p., and crop out only along the western margin of the Tirana Depression.The sequence was compared with the Langhian-Tortonian foredeep succession of the Preze homocline,which belongs to the Periadriatic Depression.The Tirana Depression differs from the Periadriatic Depression in the following developmental steps: during the late Oligocene-Aquitanian it can be considered as a narrow unstable shelf, probably forming the eastern margin of the foredeeps; during Burdigalian -early Serravallian time, it behaved as a "thrust sheet top basin", related to the front of west-vergin Dinaric thrust; during the Serravallian-Tortonian it played the role of foreland zone of the backthrust, whose ultimate enucleation is post-Pliocene in age.